(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Phrasal verbs are common in everyday English, yet many non-linguistic students find them confusing and hard to remember. The difficulty often comes from their idiomatic meanings and the fact that one phrasal verb may carry several different interpretations depending on the context. This small-scale study explores what exactly causes these challenges among non-linguistic learners. The research includes a short diagnostic test, a questionnaire, classroom observation, and informal interviews. The results show that students mainly struggle with literal translation, lack of contextual examples, and limited exposure to spoken English where phrasal verbs naturally appear. The study suggests that teachers should use more context-based explanations, visual support, and communicative tasks to help students learn phrasal verbs more effectively.